Inhibition of the Fibrinogen‐Like Protein 2:FcγRIIB/RIII immunosuppressive pathway enhances antiviral T‐cell and B‐cell responses leading to clearance of lymphocytic choriomeningitis virus clone 13. Issue 3 (20th February 2018) - Luft, Olga; Khattar, Ramzi; Farrokhi, Kaveh; Ferri, Dario; Yavorska, Nataliya; Zhang, Jianhua; Sadozai, Hassan; Adeyi, Oyedele; Chruscinski, Andrzej; Levy, Gary A.; Selzner, Nazia
Summary: Persistent viruses evade immune detection by interfering with virus‐specific innate and adaptive antiviral immune responses. Fibrinogen‐like protein‐2 (FGL2) is a potent effector molecule of CD4 + CD25 + FoxP3 + regulatory T cells and exerts its immunosuppressive activity following ligation to its cognate receptor, Fc γ RIIB/RIII. The role of FGL2 in the pathogenesis of chronic viral infection caused by lymphocytic choriomeningitis virus clone‐13 (LCMV cl‐13) was assessed in this study. Chronically infected fgl2 +/+ mice had increased plasma levels of FGL2, with reduced expression of the maturation markers, CD80, CD86 and MHC‐II on macrophages and dendritic cells and impaired production of neutralizing antibody. In contrast, fgl2 −/− mice or fgl2 +/+ mice that had been pre‐treated with antibodies to FGL2 and Fc γ RIIB/RIII and then infected with LCMV cl‐13 developed a robust CD4 + and CD8 + antiviral T‐cell response, produced high titred neutralizing antibody to LCMV and cleared LCMV. Treatment of mice with established chronic infection with antibodies to FGL2 and Fc γ RIIB/RIII was shown to rescue the number and functionality of virus‐specific CD4 + and CD8 + T cells with reduced total and virus‐specific T‐cell expression of programmed cell death protein 1 leading to viral clearance. These results demonstrate an important role for FGL2 in viral immune evasion and provide a rationale to target FGL2 to treat patients with chronic viral infection. Abstract : Building on the exciting findings demonstrating a role for FGL2 as an effector molecule of CD4 + CD25 + FOXP3 + TIGIT + Treg cells suppressing T helper type 1 and type 17 responses in vivo, the results in this report highlight an important contribution of the FGL2‐Fc γ RIIB/RIII pathway in immune suppression in an experimental model of chronic infection caused by LCMV cl‐13. We show in early infection that FGL2 is rapidly up‐regulated and contributes to T‐cell dysfunction. Targeted deletion of fgl2 or treatment with novel neutralizing antibodies to FGL2 led to a restoration of immunity with enhanced virus‐specific T‐cell numbers, increased cytokine secretion and the development of neutralizing antibodies to LCMV cl‐13 coinciding with viral clearance of an otherwise persistent infection.